Co-designing and evaluating a prenatal yoga intervention for ethnic minority women: a feasibility study - Carolina Estevao; Carola Chiarpenello; Winsze Kwok; Hemant Bhargav; Nishitha Jasti; Prabha Chandra; Shivarama Varambally; Carmine Pariante (Pilot and Feasibility Studies)
Abstract Background Prenatal depression is the greatest risk factor for postnatal depression and subsequently, impaired mother-infant attachment. Prenatal yoga may improve both mental and physical health during pregnancy and support mother–fetal attachment. However, its integration into perinatal care remains limited due to a lack of standardization. This study primarily assessed the feasibility of a prenatal yoga module co-developed by King’s College London and the National Institute of Mental Health and Neurosciences (NIMHANS). This study aimed to evaluate the feasibility of the first rigorously designed, scientifically backed prenatal yoga module for mental health and mother–fetal attachment. Methods We codeveloped the PRENAYOGA intervention through Preliminary Patient and Public Involvement (PPI) and a 3-month collaboration project with NIMHANS. The final yoga module consisted of biweekly 1-h sessions for 8 weeks in South London, with 15 ethnic minority women. Data were collected at baseline, 4 weeks, and 8 weeks. Feasibility outcomes, including intervention acceptability, appropriateness, and attendance, were assessed using validated measures and focus group data. Clinical exploratory outcomes, such as mental health and maternal–fetal attachment, quality of life, social support, and self-efficacy were also evaluated. Results The findings demonstrated the acceptability and appropriateness of the adapted yoga module among participants and stakeholders. Attendance and attrition rates alongside qualitative analyses highlighted both barriers and enablers to sustained engagement. Participants reported enhanced physical and mental health, flexibility, and relief from physical ailments. Insights into session frequency and duration suggested that two 1-h sessions per week for 8 weeks are a viable model, with 80% attending at least once weekly. Yoga teachers highlighted the community-building aspect and adapted sessions to participants’ unique needs. Preliminary clinical findings suggested improvements in mental health and maternal–fetal attachment, though these require further investigation. Conclusions These preliminary results indicate the potential benefit of rigorously developed prenatal yoga for ethnic minority populations. These findings support the need for larger trials to evaluate the module’s clinical effectiveness and scalability; such research would contribute to evidence-based prenatal care for underrepresented populations. Trial registration ClinicalTrial.gov Identifier: NCT05824208.